A Sustainable Method for the Synthesis of Acetic Acid Based on Dehydrogenation of an Ethanol–Water Solution Catalyzed by an Iridium Complex Bearing a Functional Bipyridonate Ligand. Issue 17 (7th September 2018) - Kuwahara, Masato; Nishioka, Masaaki; Yoshida, Masato; Fujita, Ken‐ichi
Abstract: The front cover artwork for issue 17/2018 is provided by Prof. Ken‐ichi Fujita′s group from Kyoto University, Japan. The image shows the synthesis of acetic acid via dehydrogenation of a mixture of ethanol and water using a new iridium catalyst bearing a functional bipyridonate ligand with N, N‐dimethylamino substituents. See the Communication itself athttps://doi.org/10.1002/cctc.201800680 . Abstract : "An efficient system for the synthesis of acetic acid via dehydrogenation of an ethanol–water solution using a new iridium catalyst" This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttps://doi.org/10.1002/cctc.201800680 .